Development of Critical-Thinking Skills Rubric within the Scope of Multicultural Education - Serkan Aslan , Birsel Aybek (Educational Process: International Journal, 2024)
Background/Purpose. The study aimed to develop a rubric to measure students’ critical-thinking skills within a multicultural education scope.